Toxic Air Pollutants and Their Effect on Multiple Sclerosis: A Review Study - Mohammadi, Mohammad Javad; Zarea, Kourosh; Hatamzadeh, Nasser; Salahshouri, Arash; Sharhani, Asaad (Frontiers in Public Health, 2022)
Toxic air pollutants are one of the main factors that have the effect of synergism to increase the incidence of multiple sclerosis (MS). This review aims to investigate the effects of toxic air pollutants on the occurrence of multiple sclerosis (MS). A narrative review of the literature was done from 2000 to 2022 based on various databases such as Google Scholar, Web of Science, Springer, PubMed, and Science Direct. In this study, according to the databases, three hundred and sixty articles were retrieved. Of these, 28 studies were screened after review and 14 full-text articles entered into the analysis process. Finally, 9 articles were selected in this study. According to the finding of this study, toxic air pollutants including polycyclic aromatic hydrocarbons (PAHs), heavy metals (HM), volatile organic compounds (VOCs), particulate matter (PM), and gases are the main agents that cause the development and spread of chronic diseases such as respiratory and cardiovascular diseases, chronic obstructive pulmonary disease (COPD), and multiple sclerosis. The result of this study showed that the main sources of emission of toxic air pollutants include industries, cars, power plants, and the excessive consumption of fossil fuels. In general, the inhalation of high concentration of toxic air pollutants can increase the risk of chronic diseases and multiple sclerosis.